THE DEVELOPMENT OF SMART CITIES IN UKRAINE IN THE CONTEXT OF GLOBAL TRENDS - UNINETS, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the features of the modern stage of the development of smart cities in the world and in Ukraine, and highlights the key prerequisites. It has been established that the formation of smart cities takes place in the conditions of global intellectualization, which is reflected in the key indexes and ratings of smart city evaluation in the world. It was determined that the weight of intellectualization factors in individual indices can reach 40% in the overall assessment. In general, within the framework of the study, the Ukrainian case of the formation of smart cities was characterized and the key forms of implementation of the smartization process of city management were analyzed. The key features of the formation of a smart management system in the cities of Kyiv, Poltava, Kharkiv, Odesa, Lviv, and Dnipro have been determined. It has been determined that at the initial stage, capital investment in the development of smart cities is key to the formation of an integrated system of smart management, which combines the need to create prerequisites for high-quality well-being, increase the competitiveness of cities and ensure sustainability. In general, the key goal of the development of smart cities involves optimizing the function of megacities, increasing the level of comfort for living in all constituent elements, including government, society, economy, ecology, lifestyle and mobility opportunities. Today’s urban environment is filled with advanced multimodal transportation systems, self-sustaining and self-managing energy networks, comprehensive services, amenities, and access to services. However, complex problems complicate the implementation of the concept of smart cities, which includes infrastructure support, the growth of the urban population and the need to implement the global goals of sustainable development. The construction of a smart city system is possible only under the condition of unification and joint work of authorities, businesses and public organizations, which is caused by the need to combine all management systems into a single network.